Profiles of Dual Language Education in the 21st Century - Arias, M. Beatriz; Fee, Molly (CAL Series on Language Education, 2018)
In the last 20 years dual language education programs have increased in number and expanded in range. Whereas once they were predominantly focused at the elementary level, they now span from pre-K through to high school. This book examines the key attributes of successful dual language programs, as well as the challenges and opportunities involved in extending the dual language instructional model to pre-K and secondary settings. Chapter authors, who are themselves both researchers and practitioners, explore the latest research and policy implications for implementation of dual language in three different contexts; within a school, a dual language school and a dual language district. This book will be of interest to teachers, teacher educators, professional development specialists, policymakers, administrators, and researchers